The Role of Endoscopic Ultrasound-Guided Ki67 in the Management of Non-Functioning Pancreatic Neuroendocrine Tumors - YongYan Cui; Lauren G. Khanna; Anjali Saqi; John P. Crapanzano; James M. Mitchell; Amrita Sethi; Tamas A. Gonda; Michael D. Kluger; Beth A. Schrope; John Allendorf; John A. Chabot; John M. Poneros (Clinical Endoscopy, 2020)
Background/Aims The management of small, incidentally discovered nonfunctioning pancreatic neuroendocrine tumors (NF-PNETs) has been a matter of debate. Endoscopic ultrasound with fine-needle aspiration (EUS-FNA) is a tool used to identify and risk-stratify PNETs. This study investigates the concordance rate of Ki67 grading between EUS-FNA and surgical pathology specimens in NF-PNETs and whether certain NF-PNET characteristics are associated with disease recurrence and disease-related death. Methods We retrospectively reviewed the clinical history, imaging, endoscopic findings, and pathology records of 37 cases of NF-PNETs that underwent pre-operative EUS-FNA and surgical resection at a single academic medical center. Results There was 73% concordance between Ki67 obtained from EUS-FNA cytology and surgical pathology specimens; concordance was the highest for low- and high-grade NF-PNETs. High-grade Ki67 NF-PNETs based on cytology (p=0.028) and histology (p=0.028) were associated with disease recurrence and disease-related death. Additionally, tumors with high-grade mitotic rate (p=0.005), tumor size >22.5 mm (p=0.104), and lymphovascular invasion (p=0.103) were more likely to have poor prognosis. Conclusions NF-PNETs with high-grade Ki67 on EUS-FNA have poor prognosis despite surgical resection. NF-PNETs with intermediate-grade Ki67 on EUS-FNA should be strongly considered for surgical resection. NF-PNETs with low-grade Ki67 on EUS-FNA can be monitored without surgical intervention, up to tumor size 20 mm.